The variation in the strength of the field during the shuttle’s motion - Levitskiy A.G.; Matveev D.A.; Potsipun A.A.; Oshina O.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to calculate the concentration of the force field in which the athlete’s center of mass shifts during the shuttle run. Methods and structure of the study. The researchers captured footage of two athletes performing shuttle drills: a jiu-jitsu master (weighing 52 kilograms and standing at 1,6 meters) and a novice athlete (weighing 30 kilograms and standing at 1,2 meters). For each athlete, the path of the center of gravity was plotted for one oscillation of the center of gravity (for one forward and backward movement), and the values of the projections of the velocities and accelerations of the centers of gravity on the coordinate axes were calculated. Results and conclusions. The differences in the force fields of a highly trained athlete and a beginner athlete were examined. The experiment revealed that the periods of divergence in the force field of a highly trained athlete are considerably longer than those of a novice athlete. Furthermore, it can be inferred that a highly trained athlete relies more on external factors (such as gravity) than a less experienced athlete.